Beyond positivism: Toward a pluralistic approach to studying "real" teams. (May 2020) - Nyein, Kyi Phyu; Caylor, Jesse R.; Duong, Ngoc S.; Fry, Trevor N.; Wildman, Jessica L.
To conduct sound research on organizational teams while overcoming the difficulties inherent in studying teams in situ, it is essential for researchers to consider all possible methodologies at their disposal. However, in the science of teams, published research is primarily driven by a positivist paradigm and quantitative methodology. This research offers an important perspective but fails to capitalize on the wide array of paradigms and methodologies outside of this perspective. Accordingly, we advocate for a pluralistic approach to studying real-world teams that utilizes qualitative methodologies to complement and enhance quantitative findings. We summarize philosophical assumptions, research paradigms, and qualitative methodologies not commonly used in research on teams. We then highlight existing qualitative research within several exemplar topic areas (team conflict, membership change, team adaptation, shared leadership, and inclusion in teams) and offer propositions for how qualitative methodologies can be used to develop a better understanding of real teams in organizations.